Олигомеризация фракции С9 под действием каталитических систем на основе TICL4; Научные труды SWORLD; Т. 15, № 2 - Ляпков А. А. Алексей Алексеевич; Ионова Е. И. Елена Ивановна; Бондалетов В. Г. Владимир Григорьевич; Петухова А. В. Анна Владимировна (2010, 2010)
Заглавие с экрана